Thermal/Mechanical measurement and modeling of bicycle disc brakes - Feier, I.; Redfield, R. (Proceedings, 2018)
Brake induced heating has become more difficult to control as bicycle component mass has been reduced. High-power braking with insufficient cooling or thermal capacitance can create excessive temperatures, boiling brake fluid, performance degradation, and damage. To better understand component heating, a disc braking dynamometer has been constructed with a motor driven disc, hydraulic braking, and a miniature wind tunnel. Disc temperatures are studied for various braking scenarios using infrared techniques and thermocouples. A transient, numerical, MATLAB, lumped parameter thermal/mechanical model is created to predict the impact of key design parameters on braking performance and to understand the heat loss mechanisms from the brake system components. Computational fluid dynamics (CFD) simulations are used to estimate the disc surface convective cooling coefficients for the model. The final model provides transient temperature predictions based on bicycle velocity and braking power, and successfully matches dynamometer experimental data.